Magnetic field-induced signal enhancement in laser-produced lead plasma. (25th March 2019) - Akhtar, M.; Jabbar, A.; Ahmed, N.; Mehmood, S.; Umar, Z.A.; Ahmed, R.; Baig, M.A.
Abstract: Laser-induced breakdown spectroscopy has been exploited to investigate the laser-produced lead plasma with and without external magnetic field. Plasma on the lead surface was generated by focusing a beam of a Nd:YAG laser (532 nm). An external magnetic field was applied across the laser-produced plasma; its value was varied from 0.3 to 0.7 T and the time-integrated spectra were captured at different time delays. Maximum enhancement in the neutral and ionic line intensities have been observed at 130 mJ laser energy. The neutral line of Pb at 368.34 nm reveals an enhancement factor of nearly 1.3, 1.6, and 2.3 at 0.3, 0.5, and 0.7 T, whereas the Pb ionic line at 424.49 nm shows enhancement factor of approximately 2.8 and 4.2 at 0.3 and 0.7 T. The magnetic field effects on various plasma parameters such as plasma temperature, electron number density, and emission line intensities have also been investigated. The plasma parameter "β" is found to be <1 in all the experimental conditions which signifies that the enhancement in the signal intensity is due to the plasma confinement. The increase in the emission signal intensity, number density as well as plasma temperature is observed with increasing laser energy and magnetic field. The spatial and temporal behavior reveals that the plasma temperature and electron number density decrease slowly in the applied magnetic field due to the deceleration of the plasma plume. The optimized conditions for the maximum plasma confinement and the emission intensity enhancement are observed at 130 mJ laser energy at 0.7 T magnetic field.